2009
DOI: 10.1271/bbb.80516
|View full text |Cite
|
Sign up to set email alerts
|

Different Profiles of Quercetin Metabolites in Rat Plasma: Comparison of Two Administration Methods

Abstract: The bioavailability of polyphenols in human and rodents has been discussed regarding their biological activity. We found different metabolite profiles of quercetin in rat plasma between two administration procedures. A single intragastric administration (50 mg/kg) resulted in the appearance of a variety of metabolites in the plasma, whereas only a major fraction was detected by free access (1% quercetin). The methylated/non-methylated metabolites ratio was much higher in the free access group. Mass spectrometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0
4

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 32 publications
3
24
0
4
Order By: Relevance
“…Interestingly, the metabolic profile after pure quercetin reported herein seems to be different from that after quercetin rich foods in humans [16,26,36] which includes quercetin-3 -O-sulfate, quercetin-3-O-glucuronide, isorhamnetin-3-O-glucuronide, quercetin diglucuronide and quercetin glucuronide sulfate while the aglycones are undetected. Similarly, different metabolites of quercetin were found in rat plasma after a single intragastric administration compared to those after free access mixed with food [37]. Thus, quercetin administration, as a capsule to humans or as an intragastrical suspension to rats, results mainly in an increase of Q3GA with minor increases in other metabolites including the aglycones.…”
Section: Discussionmentioning
confidence: 94%
“…Interestingly, the metabolic profile after pure quercetin reported herein seems to be different from that after quercetin rich foods in humans [16,26,36] which includes quercetin-3 -O-sulfate, quercetin-3-O-glucuronide, isorhamnetin-3-O-glucuronide, quercetin diglucuronide and quercetin glucuronide sulfate while the aglycones are undetected. Similarly, different metabolites of quercetin were found in rat plasma after a single intragastric administration compared to those after free access mixed with food [37]. Thus, quercetin administration, as a capsule to humans or as an intragastrical suspension to rats, results mainly in an increase of Q3GA with minor increases in other metabolites including the aglycones.…”
Section: Discussionmentioning
confidence: 94%
“…2). Quercetin-3- O -glucuronide is the major metabolite found in human and rat plasma [12, 14, 15]. It was previously shown that plasma concentrations of quercetin metabolites could inhibit myeloperoxidase [12].…”
Section: Resultsmentioning
confidence: 99%
“…Experimental quercetin supplementation has been used to counteract oxidative stress in a number of forms, including dissolved in water (14), ethanol (15) or propylen glycol (12), or food-supplemented (12). Quercetin has been used as pre-treatment to radiation in mice (16) and other flavonoids have been tested both prior to and following irradiation (17).…”
Section: Discussionmentioning
confidence: 99%